The poetics of the drama of Natalia Moshina - Головчинер, Валентина; Сумина, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper surveys the work of the Russian playwright, author of nine dramas, written in 2004–2011 and not subjected to research yet. Two of the plays (A Triangle and Under Heavens) are analysed and also compared with others. This makes possible the conclusion that the modern drama is characterized not only by breaking off with the experience of the predecessors, manifest in post-modernist provocations of „the new drama”. Natalia Moshina is presented as a talented playwright developing the potential of the intellectual, epic drama of the 20th century within the paradigm of the latest non-classical poetics.